EFEKTIVITAS MODIFIKASI KONSTRUKSI BUBU DASAR TERHADAP HASIL TANGKAPAN IKAN DI PERAIRAN PULAU LEMUKUTAN KALIMANTAN BARAT - Ho Putra Setiawan; Sadri Sadri; Agus Setiawan (Fakultas Perikanan dan Ilmu Kelautan, 2017)
Exploiting the potential of catching fish in the waters of the island of Lemukutan by using the base to catch fish trap and still are traditional. Technical aspects in this research is to modify the base where trap construction entrance on change into six and eight and the bamboo wood frame in Polyethylene nets agency change (PE) pipe frame of cast concrete picture with. The purpose of this research is Get method model, analyze the effectiveness of basic trap modification construction basic financial analysis and trap. Analysis of the composition of catches against the third type of trap get results of 84.88 kg or of 690 tail at a depth of 9 m and 95.53 kg or 800 tail at a depth of 12 m. The frequency of occurrence of the yellow tail fish (Caesio erythrogaster) had the largest proportion at a depth of 9 m long and 12 m is 86.8 % and 99.5 %. Analysis of the index of Diversity (H ‘) to the waters of the Lemukutan Island of 1.6 by category index of diversity (H ‘ ≤ 2). The results of the analysis of R/C Ratio indicates that modifications to the construction of beam model trap obtaining R/C = 1.035 where economically feasible and viable use developed as a basic fishing effort in the waters of the island of Lemukutan.